The effect of conventional exercise and single kick motion on increasing cardiovascular endurance - Muhtar Rudi, Muhamad Jamaludin; widiastuti, Widiastuti; Setiakarnawijaya, Yasep (Universitas Suryakancana, 2025)
The purpose of this study was to determine the effect of training methods and motivation on increasing cardiovascular endurance in pencak silat athletes. The research sample was 40 athletes of pencak silat in East Jakarta. The sampling technique used refers to the procedure stated by Verducci. The method used in this research is an experimental method with a 2x2 Treatment by Level Research Design. The technique used is a two-way analysis of variance with a 2 x 2 factorial design with a significance level of 0.05. In general, the results of the study based on the results of the analysis of variance, obtained a significant Fcount <0.05, a significant level, which means the research hypothesis. Thus, the increase in cardiovascular endurance can be influenced by exercise methods and motivation. For researchers who are interested in this issue, can conduct further research by trying othervariables that are quite influential on the cardiovascular endurance of pencak silat athletes, to develop research in the field of sports, especially pencak silat sports